Weeds and weed flora as the basis for phytosanitary zoning (a review) - N. N. Luneva (Труды по прикладной ботанике, генетике и селекции)
The concept of “the weed flora” is still associated with weedy plants within agricultural phytocenoses, despite the fact that its association with a wider range of secondary habitat types with disturbed vegetation and soil cover was discussed as early as in the first half of the last century. The study of this characteristic feature of weeds has been continued at the present time, which is reflected in the very concept of “the weed” adopted by the state standards. The structure of the weed flora includes groups of weedy plant species within both naturally and anthropogenically disturbed habitats, so such notions as “the segetal flora” or “synanthropic flora” do not fully reflect the composition of the weed flora. The formation of the weed flora was historically linked with the emergence and development of cultivated plants. A regional weed flora is composed of weed plant species, for which this or that region is suitable in terms of growing conditions. In the context of agriculture and plant protection, the elementary weed flora is the flora of an agricultural landscape or an agricultural ecosystem, as its component. Phytosanitary zoning for a set of weed species confined to a specific territory is carried out at the macro-, meso-, and microlevels. The criterion for identifying the levels of phytosanitary zoning is the weed flora of different territorial levels.